Description of Social Support for Postpartum Mothers Comparison of Sectio-Caesarea with Normal Birth in Kartasura Region - Luthfianto, Muhammad Najib; Rahayuningsih, Faizah Betty (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
The purpose of this study is to understand the social dynamics of a baby using conventional and sectarian sampling techniques.Cross-sectional methodology with purposive sampling as the primary sampling method was used in Kartasura Region. This study was conducted between September 28 and October 15, 2022. For the validated respondent data, there were 54 respondents between the ages of 20 and 41. The type of data collection that is used is descriptive quantitative information analysis. An instrument for doing research employs a self-contained questionnaire. Data analysis using the SPSS 25 program. Nilai is significant (p=0.05). The instrument used in this study is the Postpartum Social Support Questionnaire (PSSQ). The sampling analysis process used an Independent T-test.Results: There were 54 responses to the survey. Those who are younger than us, they are 20 and 41 years old, respectively. Out of all the respondents, 27 were adults with normal sexual orientation, and the remaining 27 had a Sectio-Caesarean birth. There were no significant differences in the social link between standard and Caesarea childbirth (2-tailed) > 0,05 (p-value 0,364), which means that there were no significant differences in the social link between postpartum mother and normal childbirth (2-tailed) > 0,05. Friend support received the highest rate of success out of the four social networking systems, which are Husband Support, In-law Support, Parent Support, and Friend Support, with a rate of success of 40,83.Applications/Originality/Value: There is no difference between an infant's social network when they give birth normally and when they give birth via cesarean section. The differences between this study and other studies may be seen in the study respondent, study time, study instrument, study literature, study method, and study result. In regards to childbirth, it can be said that the ratio of childbirth to normal childbirth is noticeably higher, and the ratio of childbirth to the fourth subset of social networks is particularly high, with a ratio of 40.83.